ডেটলাইন বাংলাদেশ : নাইন্টিন সেভেন্টিওয়ান : বাংলাদেশের মুক্তিযুদ্ধকালীন রিপোটার্জ সংকলন সিডনি শনবার্গ - শনবার্গ, সিডনি . (Sydney Hillel), 1934-; Haka, Maphidula (ঢাকা : সাহিত্য প্রকাশ, 2000)
Collection of reports published during Bangladesh's freedom movement, by Sydney Schanberg, an American journalist with The New York Times.
In Bengali.
Keywords: 1971; Bangladesh -- History -- Revolution, 1971 -- Sources; Bangladesh; History; Sources